Immunological Characteristics of Hyperprogressive Disease in Patients with Non-small Cell Lung Cancer Treated with Anti-PD-1/PD-L1 Abs - Kim, Kyung Hwan (Immune Netw, 2020)
Hyperprogressive disease (HPD) is a distinct pattern of progression characterized by acceleration of tumor growth after treatment with anti-PD-1/PD-L1 Abs. However, the immunological characteristics have not been fully elucidated in patients with HPD. We prospectively recruited patients with metastatic non-small cell lung cancer treated with anti-PD-1/PD-L1 Abs between April 2015 and April 2018, and collected peripheral blood before treatment and 7-days post-treatment. HPD was defined as ≥2-fold increase in both tumor growth kinetics and tumor growth rate between pre-treatment and post-treatment. Peripheral blood mononuclear cells were analyzed by multi-color flow cytometry to phenotype the immune cells. Of 115 patients, 19 (16.5%) developed HPD, 52 experienced durable clinical benefit (DCB; partial response or stable disease ≥6 months), and 44 experienced non-hyperprogressive progression (NHPD). Patients with HPD had significantly lower progression-free survival (p<0.001) and overall survival (p<0.001). When peripheral blood immune cells were examined, the pre-treatment frequency of CD39(+) cells among CD8(+) T cells was significantly higher in patients with HPD compared to those with NHPD, although it showed borderline significance to predict HPD. Other parameters regarding regulatory T cells or myeloid derived suppressor cells did not significantly differ among patient groups. Our findings suggest high pre-treatment frequency of CD39(+)CD8(+) T cells might be a characteristic of HPD. Further investigations in a larger cohort are needed to confirm our results and better delineate the immune landscape of HPD.